STUDENTS’ ATTITUDE TOWARD THE USE OF GOOGLE CLASSROOM ON TRANSLATION SUBJECT IN ENGLISH DEPARTMENT OF FKIP UMMY SOLOK - Marsika Sepyanda (English Language Teaching and Research, 2018)
This study aimed to know the students’ attitude toward the use of Google Classroom as an application used in collecting their assignment on Translation subject. The importance of this study was based on the development of IT and the use of mobile application as supporting media in teaching and learning process. In addition, Google Classroom has been used as supporting tool in collecting students’ assignments on several subjects taught at Department FKIP UMMY Solok. One of the subjects is Translation subject that usually contains several assignments that should be submitted by the students directly.This research was conducted by using descriptive method. The subject of this research were third year students of English Department FKIP UMMY Solok in 2017/2018 academic year consisted of 9 students. The instrument of this research was a questionnaire where the students were asked to give respond to each statement in 60 minutes. The questionnaire was based on indicators of students’ attitude that categorized into three aspects: cognitive, affective, and behavior.The result of this study found that students’ attitude toward the use of Google Classroom in collecting their assignment on Translation subject was in the “ good” level. In other word, the students’ attitude toward the use of Google Classroom on Translation subject at third year of English Department students of FKIP UMMY in 2017/2018 academic year Solok was positive. So, it can be concluded that Google Classroom can be used as an effective tool in collecting students’ assignments, especially in Translation subject.Keywords: students’ attitude, Google Classroom, translation subject